A bibliometric analysis of the role of microbiota in trauma - Huang, Runzhi; Lu, Yuwei; Jin, Minghao; Liu, Yifan; Zhang, Mengyi; Xian, Shuyuan; Chang, Zhengyan; Wang, Lei; Zhang, Wei; Lu, Jianyu; Tong, Xirui; Wang, Siqiao; et al. (Frontiers in Microbiology, 2023)
Introduction Over the last several decades, the gut microbiota has been implicated in the formation and stabilization of health, as well as the development of disease. With basic and clinical experiments, scholars are gradually understanding the important role of gut microbiota in trauma, which may offer novel ideas of treatment for trauma patients. In this study, we purposed to summarize the current state and access future trends in gut microbiota and trauma research. Methods We retrieved relevant documents and their published information from the Web of Science Core Collection (WoSCC). Bibliometrix package was responsible for the visualized analysis. Results Totally, 625 documents were collected and the number of annual publications kept increasing, especially from 2016. China published the most documents while the USA had the highest local citations. The University of Colorado and Food & Function are respectively the top productive institution and journal, as PLOS One is the most local cited journal. With the maximum number of articles and local citations, Deitch EA is supported to be the most contributive author. Combining visualized analysis of keywords and documents and literature reading, we recognized two key topics: bacteria translocation in trauma and gut microbiota's effect on inflammation in injury, especially in nervous system injury. Discussion The impact of gut microbiota on molecular and pathological mechanism of inflammation is the focus now. In addition, the experiments of novel therapies based on gut microbiota's impact on trauma are being carried out. We hope that this study can offer a birds-eye view of this field and promote the gradual improvement of it.